RESEARCH ON THE EFFECT OF TEMPERATURE RISE ON BACKLASH AND DIVIDING ACCURACY OF WORM GEAR - FENG AiPing; JING GuoFeng (Jixie qiangdu)
Based on the large size and high precision worm gear pair after the temperature rise of deformation as the research object,analyses the deformation characteristics of the deformation of parts,combined with the calculation of the different parts of the deformation,the main factors affecting backlash is determined. On the other hand to explore the influence of temperature rise on the indexing accuracy principle and level. For this kind of turntable under different temperature conditions at the time of assembly back gap value provides a calculation method,as well as provides a quantitative reference for practical use and maintenance.